SURVEY ON PROTOTHECA SPP. OCCURRENCE IN RAW MILK FROM AUTOMATIC DISPENSER: PUBLIC HEALTH CONCERN - G. Cammi (Italian Journal of Food Safety, 2011)
Prototheca spp. are colorless unicellular algae ubiquitous in nature and opportunistic pathogens for humans and animals. Since Prototheca is an important cause of bovine mastitis, milk, as well as dairy products, can be contaminated and represent a potential mean of transmission of this microorganism to man. We carried out a survey on the automatic milk dispensers in the Emilia-Romagna Region (Northern Italy), to evaluate human exposure to Prototheca through raw milk. Milk samples were collected from 177 automatic dispensers, distributing milk from 117 dairy herds. Prototheca spp. was isolated on 17 milk samples (9,6 %) produced by 14 dairy herds. The results of molecular characterization indicate that the isolates were P. zopfii genotipe 2 e P. blaschkeae, both species being associated whit human diseases. Our investigation points out the importance of raw milk as a carrier of microorganisms potentially harmful to humans.